Multiregional Oligopoly with Capacity Constraints - Alsabah, Humoud; Bernard, Benjamin; Capponi, Agostino; Iyengar, Garud; Sethuraman, Jay (Management Science, 2021)
We develop a model of Cournot competition between capacity-constrained firms that sell a single good to multiple regions. We provide a novel characterization for the unique equilibrium allocation of the good across regions and design an algorithm to compute it. We show that a reduction in transportation costs by a firm may negatively impact the profit of all firms and reduce aggregate consumer surplus if such a firm is capacity constrained. Our results imply that policies promoting free trade may have unintended consequences and reduce aggregate welfare in capacity-constrained industries. This paper was accepted by David Simchi-Levi, revenue management and market analytics.